The development of China National Geography Olympiad and the International Geography Olympiad - Wei, Dongying; Yang, Jie; Wang, Min (Journal of geographical sciences, 2014)
The International Geography Olympiad （IGEO） is a competition for the best ][6 to 19 year old students from all over the world. Four students represent each country in a series of Geography tests in （generally） a four-five day program. The aims of the IGEO are to： 1. stimulate active interest in geographical and environmental studies among young people; 2. contribute positively to debate about the importance of geography as a senior secondary school subject by drawing attention to the quality of geographical knowledge, skills and interests among young people;